Histopathological characteristics of soft tissue tumors at Madani General Hospital - Nasution, Prenan Dito Perdana; Lina, Juliana; Wardhani, Fiska Maya; Loren, Jeff; Muchtar, Muhammad Arafat; Iskandar, Ari Rahman (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Benign tumors were more common than malignant tumors, with a ratio of 1:100. However, in 2019, approximately 13,000 cases of malignant tumors were reported in the United States. Based on data from Cancer Referral Hospitals in Indonesia, soft tissue sarcomas were among the ten most common cancers in 2013, with approximately 75% of cases occurring in the extremity region. This study aimed to describe the histopathological examination results of patients with soft tissue tumors at the Madani General Hospital, Medan City. This study used a retrospective descriptive design by collecting data from the medical records of patients who underwent histopathological examination at the Anatomical Pathology Laboratory of Madani General Hospital (period 2018-2022). Data were analyzed based on the distribution of cases according to age, sex, and tumor type. The results showed that soft tissue tumors were most prevalent in the 41-50 age group with 30 patients (20.3%), the majority were female with 85 patients (57.4%), and based on histopathological diagnosis, lipoma was the most common type of tumor found in 70 patients (47.3%). All cases studied were benign tumors, with a total of 148 patients (100%).